The Common Sense as Experience of Democratic Construction: Studies in Schools in Contexts of Poverty in Chile - Redon Pantoja, Silvia; Angulo Rasco, José Félix; Vallejos, Natalia I. (Education Policy Analysis Archives, 2015)
The research presented, discussed the results with respect to the sense of the common as democratic experience in young sectors of extreme poverty in Chile. Units of study corresponded to six Chilean schools, under the design of case studies collective and instrumental collective. Product analysis of the data (speech, observation records, interviews, focus groups and documents), emerges discursive lines that coalesce around five matrices categories. In this paper, we develop a category of poverty, as the most dense and extensive. Here we found that the common sense of democratic experience fades as democratic experience in schools that reproduce the deep social cleavage posing Chile in its social fabric. Segmentation resulting in perceptions of both worlds: the "top" and "bottom". In this logic both pubic school, as the space of health, housing, neighborhood, civil protection and transport services are poor quality for a sector of the population that can not buy better quality services. In their school, in their neighbourhood, and in their social experiences, these young people go through a threatened life which is surrounded by landfills, and by the absence of the right to have rights.The loss of hope in the meritocracy (i.e. equal opportunities) is evident in their stories, which reflect the distances in their social positions, indicating that they can not compete with the cultural and social capital that gives the cradle of origin and school in the Chilean context of public policies reproduces, preventing and precluding the rise of a political and citizenship space of the common.